Transformation of Radio Technology in The Digital Age - ismandianto ismandianto; Suyanto Suyanto; Khasna Latifah; Muchid Muchid (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2022)
Radio transformation is a step to maintain existence. Innovation and adjustment to the rapid development of new media and exacerbated by the Covid-19 virus pandemic requires radio to transform into the digital era. This article aims to see the existence of RRI in transforming radio media in the digital era and Covid-19. The change of radio to the digital era is a demand in facing the challenges of progress and growth of information. This research uses descriptive qualitative method. The results show that the segmentation of radio listeners in the small category is caused by listeners who prefer and seek social media information. RRI’s strategy to uphold its existence in the digital era is to update technology and cooperation. The transformation carried out during the Covid-19 response period gave rise to an increased character for the information that was broadcast.Keywords: Transformation, technology, digital, Covid-19 ABSTRAKTransformasi radio menjadi langkah untuk mempertahankan eksistensi. Inovasi dan penyesuaian dengan perkembangan media baru yang pesat serta diperparah dengan pandemi virus Covid-19 mengaharuskan radio melakukan transformasi ke era digital. Artikel ini bertujuan untuk melihat eksistensi RRI dalam melakukan transformasi media radio di era digital dan Covid-19. Perubahan radio ke era digital merupakan tuntutan dalam menghadapi tantangan kemajuan dan pertumbuhan informasi. Penelitian ini menggunakan metode kualitatif deskriptif. Hasil menunjukkan bahwa segmentasi pendengar radio kategori kecil diakibatkan faktor pendengar yang lebih menyukai dan mencari mencari informasi sosial media. Strategi RRI menegakkan eksistensi di era digital, adalah memperbeharui teknologi dan kerjasama. Traspormasi yang dilakukan selama masa penanggulangan Covid-19 memunculkan karakter yang meningkat terhadap informasi yang disiarkan.Kata Kunci: Transformasi, teknologi, digital, Covid-19